Commercialized technology transfers from an anti-capitalist perspective [review of] - Dery, Julio C. (1977)
A review of Denis Goulet, The Uncertain Promise: Value Conflicts in Technology Transfer (New York: IDOC/North America, Inc., 1977) XIV; 318 pp.
Keywords: Book reviews; Public administration -- Economic aspects